Cohesion and Dissolution Friendship in the Globalized Punk and Hardcore Scene of Buenos Aires - Rohrer, Ingo.; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2014)
The apocryphal story of punk and hardcore is narrated as a history of young rebels united by shared interests, values and a sense of equality. Through the example of the scene of Buenos Aires, Ingo Rohrer demonstrates that this unity is fragile and requires different practices of maintenance to ensure the cohesive continuity of the community. Friendship is the focus of these efforts, but at the same time it is also a point of vulnerability where the group’s dissolution and disappointment about the scene germinates. Ingo Rohrer examines how a local scene’s quest for cohesion is concurrent with tensions and contradictions. Beyond the attention put on the friendship in the local scene, the author asks what role friendships play in the local lifeworld of neighborhoods and in the globalized punk and hardcore scene. Based on rich empirical data, the author suggests new perspectives on group processes and local/transnational relations with relevance far beyond the realm of these vibrant music scenes. Der Inhalt Punk and Hardcore – an Introduction Anthropology and Youth Theorizing Friendship Die Zielgruppen Scholars and students of sociology, cultural studies and anthropology Fans of hardcore and punk music, looking for an academic approach to the scene. Der Autor Dr. Ingo Rohrer has studied Social and Cultural Anthropology at the University of Freiburg.
Keywords: Political science; Cultural studies; Political Science; Cultural Studies